Qualidade do detrito na perda de massa do material particulado de eichhornia crassipes (mart.) solms sob efeito da temperatura - Souza, Brayan Pétrick de (2019)
Carbon cycling of macrophytes in aquatic ecosystems occurs both by the characteristics of the environment (extrinsic properties) and by the different characteristics of their debris (intrinsic properties). So, in this study, you researched a proven carbon cycling of different initial Eichhornia crassipes debris compositions and humic material formations under the effect of increasing temperature on decomposition. A plant, inoculation material and incubation water were collected in the Barra Bonita reservoir in Barra Bonita / SP. Three types of experiments were performed that contain different initial compositions of macrophyte debris: (i) natural debris, simulating or newly added debris to the sediment; (ii) remove the aqueous extract, simulating debris after a few days of decomposition; and (iii) remove the alkaline extract, simulating advanced stages of decomposition. The materials were incubated for 120 days in anaerobic and aphotic chambers, at temperatures of 20 and 28 °C. A temporal variation of the mass loss caused by experiments, parameterizes the kinetic model using the Levenberg-Marquardt iterative algorithm, and is also calculated by coefficients Q10. The statistics employed follow a significance of 5%. By mathematical model adopted, higher values of mineralized carbon and wet material training were found without decomposition experiments, including natural debris and for experiments with debris without aqueous extraction, and the values of these fractions detected in this experiment may be affected by chemical use. the initial debris suffered prior to incubation. The refractory fraction was the main non-experimental component that only removes the aqueous extract. The more refractory to debris, the more transformations are necessary for it to be incorporated by the microbial community, as demonstrated by the parameterization of the mathematical model used. Decomposition coefficients (mainly refractory refraction) were more affected by quality than temperature increase, while Q10 values indicate higher sensitivities by temperature variation for experiments without water and alkaline extraction. On these evidences, the debris quality as well as temperature contributed to the increase in mineralization values. Mathematical modeling used in experiments clearly expressed as mineralization routes of different debris. Although the increase in temperature causes a mineralization process in the aquatic environment to be accelerated, the quality of the debris was more significant.